Contrast Enhancement in Spinal MR Imaging - Breger, Robert K.; Williams, Alan L.; Daniels, David L.; Czervionke, Leo F.; Mark, Leighton P.; Haughton, Victor M.; Papke, Rose Anne; Coffer, Mary (American Journal of Neuroradiology, 1989)
We evaluated 44 patients with suspected spinal tumors or previous laminectomies with gadolinium-DTPA MR imaging in order to characterize the enhancement in normal, postoperative, and neoplastic intraspinal tissue. Using the signal intensity of CSF as an internal control, we calculated the percentage increase in signal intensity from pre- to postgadolinium studies. Tumors (astrocytoma, ependymoma, schwannoma) enhanced 70-350%; epidural scar, normal epidural venous plexus, and dorsal root ganglion enhanced up to 200%. Contrast enhancement does not per se distinguish neoplastic from normal tissue. Enhancement with gadolinium-DTPA appeared to increase the conspicuousness of intramedullary tumors but not intraosseous metastases. We believe that gadolinium-enhanced MR imaging is a valuable adjunct to routine MR imaging in the evaluation of intraspinal neoplastic processes and may be useful in delineating normal and postoperative structures in the spinal canal.